LOCUS СTANDI OF NON-PRIVILEGED APPLICANTS IN EU ANNULMENT ACTIONS - Đorđević Aleksovski, Sanja M. (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The aim of this paper is to analyze the circumstances under which private parties (natural and legal persons) can have standing in annulment actions in EU Law. The limitations imposed on them justifiably mark them as non-privileged applicants. Besides proving grounds for initiating an annulment action and the compliance with the short preclusion period, two additional conditions must be cumulatively met - that the challenged act affect non-privileged applicants in a direct and individual manner. The latter requirement, which is more difficult to achieve, is even more stringent in the Court of Justice jurisprudence. Therefore, the central part of the paper is dedicated to the analysis and criticism of Plaumann test as an extremely strictly set application test for acquiring legal standing of private parties. In light of understanding EU law as a fully rounded legal order with a complete system of protection of individual rights, the paper gives an overview of arguments and counter-arguments for its reform. It is concluded that the limiting conditions for locus standi of non-privileged plaintiffs, as well as the occasional unavailability of legal remedies before national courts, are shortcomings of EU law as an order that strives to achieve the rule of law as well as bringing the EU closer to the citizens. In the past decades the Plaumann test served as a specific tool for effectively denying standing to private parties. Although the Treaty of Lisbon has made some progress in the direction of liberalizing the acquisition of locus standi, it is only the case in a limited, narrowly defined number of situations.
Keywords: action for annulment; non-privileged applicants; standing (locus standi); Art. 263 UFEU; Plaumann test